ANALYSIS OF IMPLEMENTATION OF SHARIA INSURANCE FOR THE AGRICULTURE SECTOR - Ries Wulandari Wulandari; Nurhuda Abdullah (Institut Agama Islam Negeri Padangsidimpuan, 2021)
The allocation of financing for agricultural sector in Islamic Banking Institution is low compare to the other sector. The risk of high uncertainty, which includes the level of damage to farms and the level of crop failure, become the financing risk consideration for the banking. Rice farm insurance can be an alternative to mitigate this risk so Islamic the banking will have partner to share the risk. The insurance practice for agricultural sector has been initiated by the Ministry of Agriculture. But there are still some limitation due to the insurance inclusion and shariah compliance issues. This research provide proposal the implementation of shariah agricultural insurance with Analytical Network Methodology (ANP). The objectives of this study are 1) analyze the benefit, opportunity, cost, and risk of the implementation of Islamic agricultural insurance and 2) find the most important aspect due to the shariah agricultural insurance implementation. The research found that the most important aspect is opportunity. This insurance will give opportunity to the farmer by provide protection for the crop from the risk of harvest failure with shariah compliance and using shariah banking. The shariah scheme will help the government increasing the insurance inclusion. This scheme will benefit the farmer due to the increasing of crop insurance awareness. The requirement of this implementation comes from the cost aspect, namely legal aspect. And the risk will rise from the moral hazard as fraud claim. The results of this study indicate that the implementation of shariah insurance for the agricultural sector has opportunities and benefits, but there are still some notes to be addressed. This shariah insurance together with Islamic banking and the sustainability of agricultural sector.